Characteristic analysis and surgical exploration for acetabular roof fractures: Multicenter retrospective cohort study - Ruipeng Zhang; Yingchao Yin; Wei Chen; Yan Zhuang; Shicai Fan; Chengla Yi; Gang Lyu; Longpo Zheng; Xiaodong Guo; Ming Li; Guangyao Liu; Zhiyong Hou; et al. (PLoS ONE, 2025)
Background Acetabular roof was a crucial structure for maintaining the stability of hip joint; however, its important role was not especially emphasized in the Letournel-Judet classification system. Acetabular roof was segmented into the roof column and roof wall in Three-column classification and fracture in this area alone was defined as A3 injury. The purpose of this study was to explore the characteristics and surgical strategy of A3 injury. Methods Patients with roof column/wall fractures received surgical management from January 2015 to 2019 January at nine level-1 trauma centers were retrospectively analyzed. Fracture data, surgical incision, operation time, blood loss, fracture healing and relevant complications were recorded to explore fracture characteristics and appropriate surgical strategy. Reduction quality was assessed based on postoperative radiographic examination. Merle d’Aubigné score was used to assess the functional outcome during the follow-up. Results A total of 60 patients met the inclusion criteria in this study. Mean operation time was 112.83±21.77 min, and mean intraoperative blood loss was 396.67±182.00 ml. Satisfactory reduction quality was obtained in 49 cases (81.67%). All fractures healed well at an average mean of 3.07 months. Satisfactory outcomes were obtained in 46 cases (76.67%), and mean Merle d’Aubigné score was 15.53±1.33 points at the final follow-up. Reduction quality and functional outcome showed no statistical difference in three subtypes (P<0.05). Reduction quality and functional outcome presented positive correlation in three subtype fractures (P<0.05). The complication rate was 11.67% (7/60) in this study. Conclusion The injury mechanism of A3 injury was the direct impaction from femoral head on acetabular roof. Reduction and fixation of A3 injury were technique demanding, and poor prognosis may be accompanied even treated by experienced surgeons. Appropriate surgical strategies (Table 5) based on fracture characteristics in three subtypes of A3 injury were the premise of accepted prognosis.